Physicochemical and cooking properties of six pigeon pea (Cajanus cajan L) genotypes from Malawi - Machinjili, Tamara Tumasile; Kabambe, Vernon; Mwangwela, Agnes M. (Frontiers in Sustainable Food Systems, 2025)
IntroductionPigeon pea (Cajanus cajan) is a vital protein source in southern Malawi, yet the relationship between seed coat characteristics and cooking quality remains poorly understood. This study evaluated the influence of variety and seed coat thickness on physicochemical and cooking properties of six pigeon pea varieties: Kachangu (00040), Mwaiwathualimi (ICEAP00557), Chitedze 1 (ICEAP 01514/15), Mthawajuni, Sauma (ICP 9145), and ICPL 93026.Method and materialSeeds were obtained from ICRISAT and ChitedzeResearch Station and analyzed for water absorption, cooking time, and splitting behavior in both whole and dehulled forms.ResultsVariety significantly influenced cooking time (p < 0.001), water absorption during soaking and cooking (p < 0.001), and splitting tendency (p < 0.001). Cooking times ranged from 97 to 193 min for whole seeds versus 26–54 min for dehulled samples. Seed coat removal enhanced water absorption and reduced cooking time by 66% across all varieties. Kachangu and Mwaiwathualimi exhibited intense splitting, while thin-coated varieties showed higher aromatic intensity. Surprisingly, seed coat thickness did not significantly affect physical characteristics, water absorption, or cooking time. However, seed coat presence was the critical determinant of cooking performance.DiscussionThis study demonstrates that varietal selection combined with dehulling represents a strategic intervention for optimizing pigeon pea utilization, while enhancing nutritional accessibility and supporting sustainable food systems in resource-constrained environments. Results provide valuable insights for breeding programs targeting improved cooking quality and utilization of pigeon pea varieties for sub-Saharan Africa.